After the spring economic transitions in the Arab world - Amin, Magdi (Oxford : Oxford University Press, 2012)
For too long, the economic aspirations of the people in the region, especially young people, have been ignored by leaders in Arab countries and abroad. Competing views as to how best to meet these aspirations are now being debated in the region. The outcome will shape Arab societies for generations to come.
Description based on online resource; title from PDF title page (viewed on Apr. 20, 2012).
Keywords: Arab countries -- Economic policy -- 21st century; Arab countries -- Politics and government -- 21st century; Arab countries -- Commerce